Caracterização da resposta imunológica na infecção experimental por Toxocara canis - Thaís Leal Silva (2021)
Toxocariasis is a zoonosis, whose main etiological agent is Toxocara canis. It is a neglected, cosmopolitan disease that has a 19% seroprevalence worldwide. Humans become infected by accidental ingestion of eggs containing T. canis infective larvae, which upon reaching the intestine, hatch, penetrate the mucosa and migrate to various tissues such as liver, lungs and brain. In general, the response against helminths follows the Th2 pattern, but there are few studies that clarify the pattern of immune and pathophysiological response triggered by the host in toxocarosis. This study aimed to evaluate the immunological and pathophysiological mechanisms involved in T. canis infection in a murine experimental model, investigating the IL-33/ST2, IL-17/IL-17RA pathway and the presence of eosinophils. For this purpose, mice genetically deficient for ST2, GATA1, IL-17RA and the respective wild ones (BALB/c and C57BL/6) infected by gavage with 1000 embryonated eggs of T. canis were used, and the parasitological, immunological and pathophysiological evaluation was performed with 0 days post-infection (dpi) (control), 3dpi, 14dpi and 63dpi. The results demonstrated that ST2-/- and GATA1-/- mice during T. canis infection reduced the hepatic, pulmonary and cerebral parasite load and decreased the formation of granulomas associated with less tissue damage. On the other hand, IL-17RA-/- mice showed an increase in the pulmonary parasite load, reduced the frequency of IL-17-producing neutrophils in the bronchoalveolar lavage, and decreased the number of granulomas in the lungs. Thus, we observed that the IL-33/ST2 pathways and the presence of eosinophils induce susceptibility to infection by T. canis and increase the number of granulomas, while the IL-17/IL-17RA pathway is associated with resistance to larval migration, however induce greater formation of granulomas that can result in tissue damage.